Comments from a soccer coach during training and competition situations (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
The primary objective of this paper was to verify if there were differences in an amateur soccer coach comments targeted to athletes in training and competition situations. The behavior of a physical education teacher coaching an amateur soccer team was recorded, with a MP4 device. Coaching comments were recorded during two games and four training situations. Further, these comments were transcribed and categorized in two main categories: Negative, which is subdivided into Corrective and Ironic-Repressive comments, and Positive, which is subdivided into Reinforcing, Motivating and Instructional comments. The results indicated that the Instructional category occurred more frequently in both analysis conditions. The data shows, however, differences in the overall frequency of comments. The overall comments frequency were higher during both games than during the previous trainings situations. Furthermore, the occurrence of reinforcing feedback is infrequent, which may have implications for the students/players learning.
Keywords: Sports Psychology; Coach comments categorization; Behavior Analysis